CRIMINOLOGICAL STUDY OF THE CRIME OF ILLEGAL SOLAR SMUGGLING FOR FISHERMEN IN RIAU ISLANDS PROVINCE - Widiyani, Heni; Farhan, Muhammad Idlal; Oktapi, Deric Ninelee; Purnomo, Armando Tri Cahyo; Suryani, Dewi Ervina; Efritadewi, Ayu (LPPM STIH Putri Maharaja, 2023)
The problem of illegal distribution of diesel fuel in the Riau Islands Province is something that is no longer commonplace, this is caused by several factors which will be explained by researchers from a criminological perspective. The aim of this research is to provide study material for academics, legal observers and students regarding the distribution of illegal diesel from a criminological perspective. This research uses a normative research method with a deductive approach, examining legal norms, principles and principles, as well as related statutory provisions. This research focuses on the phenomenon of illegal diesel smuggling in the Riau Islands Province, especially by fishermen. In his analysis, the author uses criminological factors that are behind this action, such as economic factors, social environment, possible places, and habits of imitating crime. The research results show that illegal diesel smuggling in the Riau Islands Province occurs due to economic disparities and psychological factors of the perpetrators. Law enforcement of this action requires the role of various factors, including law, law enforcement, supporting facilities, community participation, and culture.